Survival analysis and prognostic factors of the timing of first antenatal care visit in Nigeria (2019)
Objectives: This study assessed the timing of the first ANC visit among pregnant women and identified its prognostic factors. Design: Data obtained from 2013 Nigerian DHS, a cross-sectional and nationally representative survey, were used. Methods: We included women who had had at least a childbirth or got a pregnancy terminated within the five years preceding the survey or currently pregnant as of the time of the survey. The outcome variable is the timing of the first ANC visit to skilled ANC service provider. Those who were either currently pregnant or lost pregnancy but have not accessed ANC were censored. Basic descriptive statistics and survival analysis techniques involving four models were used to analyze the data at p = 0.05. Data was weighted and adjustment made for survey design and sampling errors. Results: Almost half of the respondents were aged 25–34 years. Only 65.5% had at least one contact with skilled ANC providers and such visits were initiated mostly (58%) in the second trimester. The overall incidence rate of accessing ANC per month is 110 per 1000 women. Women with higher education had a higher adjusted hazard of accessing ANC than uneducated women (aHR = 2.89, 95% CI: 2.68–3.11). Older women from households in richer wealth quintile are more likely to initiate ANC. Women from households in richer wealth quintiles, those who had no problem in accessing ANC facilities, those with higher education, residing in urban areas and in the Southern region had a higher tendency of earlier ANC initiation. Conclusion: ANC utilization in Nigeria is low and the timings of first visits are delayed. For Nigeria to achieve timely and adequate use of ANC services, health facilities should be more accessible and women should be empowered in terms of education, autonomy, and earnings in addition to changes in social cultural practices that prevent ANC uptakes.